High-triplet-energy host materials derived from directly-coupled carbazole-pyridoindole moieties. (July 2016) - Byeon, Sung Yong; Lee, Jun Yeob
Abstract: Directly-coupled carbazole-pyridoindole moieties containing host materials for green and blue phosphorescent organic light-emitting diodes were synthesized by linking the two moieties via two different positions on the carbazole-pyridoindole core structure. The carbazole-pyridoindole moieties were functionalized using benzonitrile and phenyl substituent groups to introduce controlled-charge transport properties. The host materials synthesized using the carbazole-pyridoindole moieties showed a maximum quantum efficiency of 19.1% in green phosphorescent devices, and 18.2% in blue phosphorescent devices. Graphical abstract: Highlights: Directly linked carbazole-pyridoindole core structure for host material High triplet energy host materials with thermal stability Benzonitrile and phenyl modification to manage charge transport properties